1999
DOI: 10.1001/archopht.117.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Thrombophilia and Hypofibrinolysis

Abstract: Objective: To determine whether heritable thrombophilia and hypofibrinolysis were risk factors for retinal vein occlusion. Design: Measures of thrombophilia (increased likelihood of thrombus formation) included anticardiolipin antibodies (IgG and IgM), the lupus anticoagulant (including dilute Russell viper venom clotting time), antigenic proteins C and S, and homocysteine. Polymerase chain reaction assays were performed for 3 thrombophilic gene mutations (factor V Leiden, methylenetetrahydrofolate reductase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 34 publications
2
34
1
1
Order By: Relevance
“…However, it was pointed out by Vine30 that the patient group was highly selected, having being referred and hospitalised specifically for a thrombotic examination. This was also true of a study by Glueck et al 11 who found a positive correlation in a population of patients with retinal venous occlusions (mean age of 52 years) which included 24% with a history of thrombotic events. The only study not apparently biased and which found a positive correlation was a case controlled study by Albisinni et al 31 but this had a lower prevalence of the mutation (11.1% v 1% controls, compared to 18% v 3% controls by Glueck et al 11 and 29% v 9% controls by Greiner et al 29 in the affected population).…”
Section: Factor V Leidensupporting
confidence: 64%
See 2 more Smart Citations
“…However, it was pointed out by Vine30 that the patient group was highly selected, having being referred and hospitalised specifically for a thrombotic examination. This was also true of a study by Glueck et al 11 who found a positive correlation in a population of patients with retinal venous occlusions (mean age of 52 years) which included 24% with a history of thrombotic events. The only study not apparently biased and which found a positive correlation was a case controlled study by Albisinni et al 31 but this had a lower prevalence of the mutation (11.1% v 1% controls, compared to 18% v 3% controls by Glueck et al 11 and 29% v 9% controls by Greiner et al 29 in the affected population).…”
Section: Factor V Leidensupporting
confidence: 64%
“…Likewise, a study of 102 patients found a positive correlation between MTHFR homozygosity and retinal vein occlusion (OR 1.9; 95% CI 0.95–3.81) 37. Conversely, Glueck et al 11 in a study of 14 patients with retinal venous occlusions could not confirm this association and a study of 116 Scandinavian patients did not find any difference in either the prevalence of the mutation or hyperhomocysteinaemia between controls and patients with central retinal vein occlusions, even if all patients over 50 were excluded 59. Furthermore, a recent retrospective case control study of 174 Irish patients found that a homozygous MTHFR genotype did not increase the risk of retinal or arterial vein occlusion 60.…”
Section: Methylenetetrahydrofolate Reductase (Mthfr) Mutationmentioning
confidence: 94%
See 1 more Smart Citation
“…Lupus Anticoagulans (LAC), anti-cardiolipin antibodies (ACA) and anti-beta-2-glycoprotein I IgG/IgM are commonly considered risk factors for VTE and ATE. Coniglio et al [19] and Glueck et al [20] concluded that significant percentage of LAC and ACA were present in patients with RVO, but Marcucci et al [9] have found no differences between patients and controls. Currently the role played of LAC and ACA in the RVO is still contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies associating estrogen–progestin oral contraceptives with CRVO or CRAO are case reports of only one to three cases 18,2123. Most reports of CRVO or CRAO associated with estrogens or estrogen agonists814,18–21 have not assessed interactions between pharmacologic thrombophilia conferred by estrogens or estrogen agonists and the inherited and acquired thrombophilia15,16,2435 known to be causally associated with RVO.…”
Section: Introductionmentioning
confidence: 99%